Tradition and renovation: the formation of Balmes and Martí d’Eixalà in their historic context - Ramis Barceló, Rafael; M. Vilasojana, Josep (Journal of Catalan Intellectual History, 2014)
Jaume Balmes and Ramon Martí are certainly the most profound of the Catalan thinkers in the first half of the 19th century. This work shows some of the keys to contextualize their contributions, using the influences they received as a starting point. The basic objective of the comparison is to show that, although they come from similar sources, their positions in regard to combining tradition and modernity are different. The analysis ends with a paradox: Balmes, a more noted philosopher, did not enjoy the same level of direct influence as Martí d’Eixalà. keywords Ramon Martí d’Eixalà, Jaume Balmes, XIXth education.